Influence of abiotic and biotic factors on the response of benthic macroinvertebrates to metals - Kiffney, Peter Michael, author; Clements, Will, advisor; Fausch, Kurt D., committee member; Kondratieff, Boris C., committee member; Chapman, Phillip, committee member (Colorado State University. Libraries, 1995)
Stream ecologists are well aware that chemical, biological, and physical characteristics of lotic systems vary spatially and temporally. With this in mind, I designed a series of experiments and field studies to examine the role of spatial variation in stream benthic macroinvertebrate communities in response to metals. Specifically, I tested the hypothesis that stream invertebrate communities from pristine streams of different size and altitude varied in their response to metals. To evaluate how metals affected biotic interactions, I manipulated invertebrate density, predation intensity, and metals in stream microcosms. Using stream invertebrate communities, I also designed an experiment and field survey to identify reliable bioindicators of metal contamination in western streams. Results from microcosm experiments and field studies showed that benthic invertebrate populations from high-altitude streams were more sensitive to the effects of metals than invertebrate populations from low-altitude streams. For example, Baetis sp. and Rhithrogena hageni from Little Beaver Creek (LBC), Colorado, (high-altitude stream) were significantly more sensitive to zinc than the same species from the South Fork of the Poudre River (SFP) (low-altitude stream) in stream microcosms. Results from field surveys showed that densities of most groups of aquatic insects (e.g., Ephemeroptera, Plecoptera, Trichoptera) were lower at high-altitude metal contaminated streams than those same groups at low-altitude streams. Other factors, such as variation in water temperature or nutrient concentrations between high- and low-altitude streams, could be lll responsible for these differences. However, because invertebrate responses were similar under controlled and field conditions, I hypothesize that differences in abundances between reference and contaminated locations was a result of metals. To determine if body size contributed to the variation in sensitivity of insects to metals, size measurements were made on species collected from LBC (high-altitude) and SFP (low-altitude). Measurements were also made on species from control and metal-treated stream microcosm. Most species were smaller at LBC (high-altitude stream) than the same species from SFP (low-altitude stream). For example, the mayfly Baetis tricaudatus and the caddisfly Arctopsyche grandis were significantly larger at SFP than LBC. In addition, insect body size was larger in metal-dosed microcosms than in controls. Brachycentrus sp., B. tricaudatus, R. hageni, Eohemerella infrequens, and P. badia were significantly larger in metal-treated microcosms than in controls. Logistic regression indicated survival in metal-dosed microcosms was less for small individuals than for larger individuals of the same species. These results suggest that some insect species from high-altitude streams were smaller than those from low-altitude streams, and that survival was greater for larger lifestages. Thus the variation in response of macroinvertebrates between different altitude streams observed in earlier studies may be due to differences in body size. The effects of low levels of metals (half the chronic levels of Cd, Cu, and Zn) on some species varied in relation to invertebrate density (low and high density) and invertebrate predation (no predators added and predators added). The abundance of Hydropsyche sp. was significantly lower in metal-dosed, high density treatments than in control, high density treatments. Moreover, the effects of an invertebrate predator (Hesperoperla pacifica) on Hydropsyche sp. was significantly greater in metal-dosed microcosms than in controls. These results suggest that metals interact with biotic factors to influence stream invertebrate community structure, and that effects occurred at metal concentrations lower than chronic criteria value. Toxicity experiments in stream microcosms showed that the abundance and species richness of aquatic insects were significantly reduced at 1x, 5x and 10x the United States Environmental Protection Agency chronic levels of cadmium, copper, and zinc (1x=1.1, 5.0, and 110 μg/L Cd, Cu, and Zn, respectively). Mayflies were the most sensitive group, as the abundance of Baetis sp. and Rithrogena hageni were significantly reduced in the Ix treatment. The response of Drunella grandis was size dependent, as small lifestages were significantly more sensitive than large lifestages. Stoneflies were also affected, but their response was more variable with abundances of some species (Pteronarcella badia) being reduced in the Ix treatment, whereas other species were unaffected (Sweltsa sp.). Heptageniid mayflies were consistently less abundant downstream of sources of metal contamination in the Arkansas and Eagle rivers, whereas the response of other measures were more variable. For instance, species richness and total density were greater at a metal-contaminated site on the Arkansas River compared with an upstream reference site. Therefore, results from this experiment and field survey suggest that changes in abundance of heptageniid mayflies may provide a reliable indicator of metal-contamination in western streams.
Covers not scanned.
Keywords: Stream ecology; Aquatic insects; Metals -- Toxicology